Development of Physics E-Jobsheet Integrated STEM Approach to Promote Students’ 21st Century Skills - Hanana Laila Burhan; Asrizal Asrizal; Ramli Ramli (Postgraduate, University of Mataram, 2025)
The development of science and technology that is developing very quickly is challenge for the world of education to prepare students who are able to compete in the current era of revolution. This research aims to produce product in the form of a class XI high school physics e-jobsheet integrated with a STEM approach to improve the skills of 21st century students. The type of research used R&D research with the development model used in this study The development model used is the ADDIE development model. Data collection techniques used are observation, interview, and questionnaire methods. Based on the data that has been analyzed, three conclusions can be drawn. First, at the analysis stage, four analysts were carried out, the results of the analysis of graduate competency standards analysis of learning activities, analysis of participant characteristics, and analysis of 21st century skills. Second, the validation result is 0.76 with valid category. Third, the results of practicality by educators are 81 with very practical category, for the results of practicality by education participants are 83.53 with categories Very practical. The results of the study concluded that the integrated physics e-jobsheet STEM approach is valid and practical for use in learning